ANALISIS PENGARUH PROFITABILITAS, LEVERAGE, DAN GCG TERHADAP TAX AVOIDANCE DAN PERBEDAAN TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR MAKANAN DAN MINUMAN DI BURSA EFEK ASEAN SEBELUM DAN SELAMA PANDEMI COVID-19 - Tan, Arneta Wynne Susilo (Accounting Study Program, Universitas Ciputra Surabaya, 2023)
The purpose of this study is to determine the effect of profitability, leverage, and good corporate governance on tax avoidance and differences in tax avoidance levels before and during the Covid-19 pandemic. This study uses a population of manufacturing companies in the food and beverage sub-sector listed on the ASEAN stock exchange in 2019 and 2020. The sample in this study was selected using a purposive sampling technique. The data analysis method of this research is using classical assumption test, multiple regression test, and different test. Profitability variable is measured by ROA, leverage is measured by DER, and tax avoidance is measured by ETR (tax burden divided by profit before tax). This study uses company size as a control variable. GCG variables are proxied into the audit committee, audit quality, and executive compensation. The results of this study are as follows: profitability has a significant negative effect on tax avoidance, leverage, audit committees, and executive compensation have no effect on tax avoidance, audit quality has a significant positive effect on tax avoidance. While the size of the company has no effect on tax avoidance as a control variable.